When deriving the general solution for the heat and wave equations, we have a constant $c$ that is carried in our calculations. Take the wave equations, for example:

$$\frac{\partial^2{u}}{\partial^2{t}} = c^2 \frac{\partial^2{u}}{\partial^2{x}}$$

Let's say we have boundary conditions $u(0, t) = 0$ and $u(1, t) = 0$.

Now assume a solution of the form

$$u(x, t) = X(x)T(t)$$

The boundary conditions imply that

$$X(0) = X(1) = 0$$

We substitute the assumed form of the solution into the PDE and use separation of variables:

$$\frac{1}{c^2} \frac{1}{T(t)} \frac{d^2T}{dt^2} = \frac{1}{X} \frac{d^2 X}{dx^2}$$

This must be equal to a constant. Make the constant $- \lambda$:

$$\frac{1}{c^2} \frac{1}{T(t)} \frac{d^2T}{dt^2} = \frac{1}{X} \frac{d^2 X}{dx^2} = -\lambda$$

The eigenvalue problems become either

$$c^2 \frac{1}{X} \frac{d^2 X}{dx^2} = - \lambda$$


$$\frac{1}{c^2} \frac{1}{T(t)} \frac{d^2T}{dt^2} = - \lambda$$

Does it matter which equation takes the constant $c$? Will we get the same solutions either way?

We are trying to derive the general series solution, so why would it matter where we put the $c$? Shouldn't it produce the same general solution either way? Otherwise, I don't think it would be 'general'?

  • $\begingroup$ Why don't you try both ways to see what happens? $\endgroup$ – mattos Jul 26 '18 at 3:18
  • $\begingroup$ @Mattos Yes I think I will do this. But can you tell me what outcome I am supposed to get so that I know where I am heading towards? $\endgroup$ – Wyuw Jul 26 '18 at 3:19
  • 1
    $\begingroup$ If you let the $c$ be with the eigenvalue problem in $X$, then the eigenvalues will be $(n \pi/c)^{2}, n \ge 1$. If you let $c$ be with the eigenvalue problem in $T$, then the eigenvalues will be $(n \pi)^{2}, n \ge 1$ i.e the $c$ is just a rescaling of the eigenvalues. $\endgroup$ – mattos Jul 26 '18 at 3:23
  • 1
    $\begingroup$ I mostly put the $c$ with the $T$ eigenvalue problem. This is because the eigenvalue is derived from the boundary value problem and so it is more convenient to have this ODE be as simple as possible. $\endgroup$ – mattos Jul 26 '18 at 3:30
  • $\begingroup$ @Mattos Hmm ok. I will do the calculations and see how this works out. Thank you for that. $\endgroup$ – Wyuw Jul 26 '18 at 3:47

In general you should get the following

$$\frac{1}{c^{2}}\frac{1}{h}\frac{d^{2}h}{dt^{2}} = \frac{1}{\phi} \frac{d^{2}\phi}{dx^{2}} = -\lambda \tag{1} $$ which gives you two eigenvalue problems

$$ \frac{d^{2}h}{dt^{2}} = -\lambda c^{2} h \tag{2} $$


$$ \frac{d^{2}\phi}{dx^{2}} = -\lambda \phi \tag{3} $$

then you end up with your boundary conditions

$$ BC1: \phi(0) = 0 \\ BC2 : \phi(1) =1 \tag{4} $$

Now if $\lambda >0$

$$ h(t) = c_{1} \cos(c\sqrt{\lambda}t) + c_{2}\sin(c\sqrt{\lambda}t) \tag{5}$$

when $\lambda = 0$ we have instead

$$ h(t) = c_{1} +c_{2}t \tag{6}$$

If $\lambda< 0$ then we get hyperbolics, addressing the question. If we change this does it matter? What is the actual solution? Consider when the boundary conditons below

$$ BC1: u(0,t) = 0 \\ BC2 : u(L,t) = 0 \tag{7} $$

Ok if we solve for them.

$$ \frac{d^{2}\phi}{dx^{2}} = -\lambda \phi \tag{8} $$


$$ \frac{d^{2}\phi}{dx^{2}} + \lambda \phi = 0 \tag{9} $$

The solutions are simply of the forms

$$ \phi(x) = c_{1}\cos(\sqrt{\lambda}x) + c_{2}\sin(\sqrt{\lambda}x) \tag{10} $$ when we use the boundary conditions we get sines with these eigenvalues

$$ \lambda = \big(\frac{n\pi }{L}\big)^{2} \tag{11} $$

so we have

$$ \phi(x) = c_{1}\sin(\frac{n\pi x}{L}) \tag{12} $$

similarly, when we find $h(t)$ comes out as above.

$$ h(t) = c_{1} \cos(c\sqrt{\lambda}t) + c_{2}\sin(c\sqrt{\lambda}t) \tag{13}$$

Note that boundary conditions made on $x$ not on $t$. So the ansatz is a product of these

$$ u(x,t) = \phi(x)h(t) \tag{14}$$ we denoted that it was any linear combinations of them. What that really means is take the product of these eigenfunctions as a basis and sum them infinitely.

$$ u(x,t) = \sum_{n=1}^{\infty} \bigg( A_{n}\sin(\frac{n\pi x}{L}) \cos(\frac{n\pi ct}{L}) + B_{n} \sin(\frac{n\pi x}{L}) \cos(\frac{n\pi ct}{L})\bigg) \tag{15} $$

Ok, so if you change where the $c^{2}$ is we have

$$ u(x,t) = \sum_{n=1}^{\infty} \bigg( A_{n}\sin(\frac{n\pi c x}{L}) \cos(\frac{n\pi t}{L}) + B_{n} \sin(\frac{n\pi cx}{L}) \cos(\frac{n\pi t}{L})\bigg) \tag{16} $$

Which I will take a moment to note that this is not the same equation.

Typically we have a initial condition right. It goes like this

$$ IC1: u(x,0) = f(x) \\ IC2 :\frac{\partial u}{\partial t}u(x,0) =g(x) \tag{17} $$

Now, not what we haven't solved for above. The coefficients. When we solve for them the major differnce appears. If I use the equation one line $15$

$$ A_{n} = \frac{2}{L} \int_{0}^{L} f(x) \sin(\frac{n \pi x}{L})dx \tag{18} $$ $$ B_{n}\frac{n \pi c}{L} = \frac{2}{L} \int_{0}^{L} g(x) \sin(\frac{n \pi x}{L})dx \tag{19} $$

This changes when you switch that clearly.


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.